Antinociceptive, Anti-Inflammatory, and Antipyretic Activity of Mangrove Plants: A Mini Review - J. A. Shilpi; M. E. Islam; M. Billah; K. M. D. Islam; F. Sabrin; S. J. Uddin; L. Nahar; S. D. Sarker (Advances in Pharmacological Sciences)
Mangrove plants are specialised plants that grow in the tidal coasts of tropic and subtropic regions of the world. Their unique ecology and traditional medicinal uses of mangrove plants have attracted the attention of researchers over the years, and as a result, reports on biological activity of mangrove plants have increased significantly in recent years. This review has been set out to compile and appraise the results on antinociceptive, anti-inflammatory, and antipyretic activity of mangrove plants. While the Web of Knowledge, Google Scholar, and PubMed were the starting points to gather information, other pieces of relevant published literature were also adequately explored for this purpose. A total of 29 reports on 17 plant species have been found to report such activities. While 19 reports were on the biological activity of the crude extracts, 10 reports identified the active compound(s) of various chemical classes of natural products including terpenes, steroids, and flavonoids. This review finds that antinociceptive, anti-inflammatory, and antipyretic activity appears to be widespread in mangrove plants.